VERIFICATION METHOD AND VERIFICATION SYSTEM FOR INTERAL ORGAN MODEL - KITAMURA, Yasuhiko; TOKIWA, Shinichi; HATANAKA, Katsunori; TAKEDA, Masatoshi; SHIRAISHI, Isao; OE, Kazuyoshi (2018)
This verification method for an internal organ model comprises: fabricating an organ model A on the basis of 3D organ data that is 3D shape data obtained by measuring the internal organ of a subject; maintaining the organ model A in a substantially similar condition as the internal organ in the body; measuring the organ model maintained in the same condition as the internal organ to obtain 3D model data which serves as the 3D shape data thereof; and displaying an internal organ shape represented by the 3D organ data and an organ model shape represented by the 3D model data to allow for comparison of the shapes. L'invention concerne un procédé de vérification pour un modèle d'organe interne, comprenant : fabrication d'un modèle d'organe A sur la base de données d'organe 3D qui sont des données de forme 3D obtenues en mesurant l'organe interne d'un sujet ; maintien du modèle d'organe A dans une condition sensiblement similaire à celle de l'organe interne dans le corps ; mesure du modèle d'organe maintenu dans la même condition que l'organe interne afin d'obtenir des données de modèle 3D qui servent de données de forme 3D de celui-ci ; et affichage d'une forme d'organe interne représentée par les données d'organe 3D et d'une forme de modèle d'organe représentée par les données de modèle 3D pour permettre une comparaison des formes. 被験者の体内器官を測定して得られた形状３Ｄデータである器官３Ｄデータに基づいて器官モデルＡを作製し、該器官モデルＡを前記体内器官の体内での態様と略同じ態様で維持し、態様を維持された前記器官モデルを測定してその形状３Ｄデータであるモデル３Ｄデータを取得し、前記器官３Ｄデータが示す体内器官形状と前記モデル３Ｄデータが示す器官モデル形状とを比較可能に表示出力するようにした。